Design and Development of Sun Energy with Solar Cell and Distillation Systems to Convert Sea Water to Be Salt and Fresh Water - Anang Widiantoro; Dwi Songgo Panggayudi (Fakultas Teknik Universitas Bhayangkara, 2018)
Solar cell is a renewable energy that utilizes solar energy sources. Energy is widely developed forvarious activities, especially for lighting. Researchers are interested in applying in other fields. That is utilizingsolar cell energy to make salt and fresh water from sea water.The principle of this system is the solar cell change sunlight becomes energy, then stored in thebattery and in the converter into an AC voltage source to be connected to a heater. This heater serves as aheating for seawater which has been designed in such a way that there is a distillation pipe (distillation) to draincooled water vapor to produce fresh water.The results of this study are expected to be a solution or alternative from renewable energy toproduce multi-use products, it’s salt and fresh water.